Major Trends in Theoretical and Applied Linguistics 1 - Sougari, Areti Maria (Selected Papers from the 20th ISTAL, 2014)
In the three volumes of Major Trends in Theoretical and Applied Linguistics, the editors guide the reader through a well-selected compendium of works, presenting a fresh look at contemporary linguistics. Specialists will find chapters that contribute to their fields of interest, and the three-volume collection will provide useful reading for anyone interested in linguistics. The first volume explores theoretical issues dealing with phonetics-phonology and syntax-semantics-morphology. Volume two is organized into three main sections that examine interdisciplinary linguistics: discourse analysis, gender and lexicography; language acquisition, and language disorders. Finally, volume three focuses on applied linguistics - both language teaching/ learning and education.